‘Living’ database of stakeholders influencing the food system at different governance levels in Honduras - International Center for Tropical Agriculture (Bioversity International and the International Center for Tropical Agriculture, 2022)
The SHIFT project is undertaking a mapping of key stakeholders with whom the project needs to engage with in order to achieve food system transformations. This " Living database" corresponds to the step 1 of this Stakeholder mapping process. It includes actors involved in decision making and implementation of activities shaping different components of the food system in Honduras. Stakeholders from public and private organisations, formal and informal sectors, government and non-governmental institutions are identified at different governance levels; including their specific areas and issues of focus in the food system, activities implemented and/or products produced, the contact person and email addresses. Future activities include conducting key informant interviews and document analysis to ensure that a diverse range of food system actors are documented.